Refractive errors in premature infants with retinopathy of prematurity after anti-vascular endothelial growth factor (anti-VEGF) therapy - Vujanović, Milena S.; Stanković-Babić, Gordana Lj.; Oros, Ana; Zlatanović, Gordana D.; Jovanović, Predrag; Cekić, Sonja P.; Tomašević, Branislav; Djorđević-Jocić, Jasmina M. (Vojnosanitetski pregled, 2017)
Background/Aim. Retinopathy of prematurity (ROP) is a vasoproliferative retinopathy which affects the blood vessels of the retina during its development. The aim of this study was to evaluate the incidence and the degree of refractive errors in premature infants with severe ROP treated with anti-vascular endothelial growth factor (anti-VEGF) (bevacizumab). Methods. This prospective study included 21 patients (42 eyes) nine months old who received intravitreal injection of anti-VEGF therapy. The control group consisted of 45 patients (90 eyes) who were subjected to laser treatment. In cycloplegia each patient underwent retinoscopy, keratorefractometry, and A-scan ultrasonography. Results. Myopia was present in 47.62% of the eyes in the study group and in 33.33% of the eyes in the control group, but there were no statistically significant differences between these groups. Seven (16.67%) eyes in the study group and 17 (18.89%) eyes in the control group were discovered to have high myopia (SE–spherical equivalents < -3.0 D – dioptre). Clinically significant hypermetropia was higher in the study group (47.62%) than in the control group (34.44%), but with no statistically significant difference. In addition, high hypermetropia was significantly greater in the control group (15.56%) than in the study group (11.90%) (p
Keywords: retinopathy of prematurity; refraction; ocular; diagnostic techniques and procedures; myopia; astigmatism; vascular endothelial growth factors